Impaired right and left ventricular mechanics in adults with pulmonary hypertension and congenital shunts. Issue 3 (March 2016) - Toro, Rocio; Cabeza-Letrán, Maria Luisa; Quezada, Maribel; Rodriguez-Puras, Maria Jose; Mangas, Alipio
Abstract : Aims: To assess left ventricle mechanics in Eisenmenger physiology patients with congenital shunts, and their relationship with the right ventricle, and to consider the clinical usefulness of this information. Methods: The study involved 28 patients with pulmonary artery hypertension (PAH) and congenital shunt, matched with 28 healthy participants. Standard echocardiography and pulsed wave tissue Doppler imaging were employed to analyze systolic and diastolic ventricular function, the myocardial performance index (MPI) of ventricles, and the strain and strain rate along the left ventricle lateral wall, septum, and right ventricle free wall. Results: The left ventricle ejection fraction was similar in the two groups. However, despite normal standard left ventricle measures, patients presented parameters of defective myocardial mechanics: mitral peak systolic velocity (S′) (cm/s) (8.6 (7.6–10.9) vs. 10.7 (8.6–12.5); P = 0.002) was higher, whereas left ventricle-MPI was lower (0.54 ± 01 vs. 0.32 ± 0.07, P < 0.001). Right ventricle-MPI and right ventricle global strain were correlated significantly with left ventricle-MPI and left ventricle global strain ( r = 0.74, P < 0.001; r = 0.442, P < 0.001, respectively). Clinically, the six-minute walking test results were correlated negatively with left ventricle-MPI ( r = −0.69, P < 0.001), whereas the functional class was positively correlated ( r = 0.36, P < 0.001). In conclusion, left ventricle mechanics and geometry are impaired in Eisenmenger syndrome patients, although conventional evaluation is in the normal range. Our results highlight the significance of ventricular interdependence in PAH and provide a useful tool for improving the clinical management of these patients.